Discrete breathers in square lattices from delocalized nonlinear vibrational modes; Physical Review E; Vol. 107, iss. 3 - Naumov E. K.; Bebikhov Yu. V.; Ekomasov E. G.; Soboleva E. G. Elvira Gomerovna; Dmitriev S. V. (2023, 2023)
Title screen